Information tecnology and telecommunications. . --. - European Union. European Commission. Directorate-General XIII - Telecommunications, Information Market and Exploitation of Research (Catalogue,Commission of the European Communities)
Resumo: Catalogo de publicacoes na area de tecnologia da informacao e teleconomicacoes.